Complete Genome Sequence and Methylome Analysis of Micrococcus luteus SA211, a Halophilic, Lithium-Tolerant Actinobacterium from Argentina - Martínez, Fabiana Lilian (2019)
Micrococcus luteus has been found in a wide range of habitats. We report the complete genome sequence and methylome analysis of strain SA211 isolated from a hypersaline, lithium-rich, high-altitude salt flat in Argentina with single-molecule real-time sequencing.